Online Game Addiction and Student Social Interaction: Re-examining the Assumptions of Social Dysfunction in the Digital Era - Dania Aulia Syaharani; Farkhan Abdurochim Alfarauq; Syaripulloh; Zaharah (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
Online game addiction is often assumed to be the cause of decreased social interaction because it is considered to reduce the intensity of real-world social relationships. However, several studies show inconsistent results, making it necessary to re-examine this assumption. This study aims to analyze the influence of online game addiction on students' social interactions and to explain this phenomenon through the perspective of Network Society. The study uses an associative quantitative approach involving 79 Social Science Education students at UIN Syarif Hidayatullah Jakarta who are active online game players and were selected using purposive sampling techniques. Data was collected through a Likert scale-based questionnaire and analyzed using validity, reliability, normality, linearity tests, simple linear regression, t-tests, and coefficient of determination. The research results show that online game addiction does not have a significant effect on students' social interaction (t = 1.060; p = 0.293 > 0.05). The determination coefficient value (R² = 0.014) indicates that online game addiction only explains 1.4% of the variation in social interaction. These findings suggest that the assumption of social dysfunction due to online game addiction is not entirely relevant in the context of a digital society. From the perspective of the Network Society, social interaction does not experience decline but rather a transformation of the arena from physical space to digital network-based space.